Knowledge socialism in the COVID-19 era: A collective exploration of needs, forms, and possibilities. Issue 6 (12th May 2022) - Crain, Daniel E.; Hollings, Stephanie; Kayode, Hazzan Moses; Ogunniran, Moses Oladele; Worapot, Yodpet; Guañuna, Paola; Yasmeen, Tahira; Riaz, Anum; Samilo, Artem; Jiang, Yuhan; Bolanle, Ogunyemi Folasade; Jackson, Liz; et al.
Abstract: The inspiration for this collective writing project began with a digital conference entitled 'Knowledge Socialism, COVID-19 and the New Reality of Education' held at Beijing Normal University. In this conference and through this article, multiple researchers spread across six continents have engaged in the collaborative task of outlining emerging innovations and alternative contingencies towards education, international collaboration, and digital reform in this time of global crisis. Trends associated with digital education, knowledge openness, peer production, and collective intelligence as articulated by Michael A. Peters' conception of Knowledge Socialism are given careful analysis and exploration. Some of the members of this collective endeavor to identify problems, others, begin to draw boxes around potential solutions. Overall, this article engages with real world challenges and innovations that look beyond dominant neoliberal trends in the knowledge economy to build bridges toward novel possibilities in this era of rapid digital change.